2010
DOI: 10.1007/s12439-010-0219-z
|View full text |Cite
|
Sign up to set email alerts
|

Kwaliteit van leven bij dementie

Abstract: Different definitions of quality of life (QOL) are found in the literature. This raised the question which domains are viewed as really important by persons with dementia. In an explorative study the opinions of persons with dementia (community-dwelling and living in nursing homes), were compared to those of professional carers and instruments for QOL in dementia. Data were gathered through interviews, focus groups and literature study. Most QOL-domains mentioned as important by persons with dementia were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…For this reason, self-rating of the QoL is often replaced by proxy rating. However, it has been shown that there could be differences on QoL ratings between patients, caregivers and theoretical models [ 48 ]. Caregivers consistently rate the patient’s QoL lower [ 14 ],[ 49 ], not only because of cognitive function [ 22 ],[ 50 ],[ 51 ] but also because of the caregiver’s burden or depression [ 22 ],[ 49 ],[ 50 ],[ 52 ],[ 53 ] and the patient’s depressive symptoms [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, self-rating of the QoL is often replaced by proxy rating. However, it has been shown that there could be differences on QoL ratings between patients, caregivers and theoretical models [ 48 ]. Caregivers consistently rate the patient’s QoL lower [ 14 ],[ 49 ], not only because of cognitive function [ 22 ],[ 50 ],[ 51 ] but also because of the caregiver’s burden or depression [ 22 ],[ 49 ],[ 50 ],[ 52 ],[ 53 ] and the patient’s depressive symptoms [ 54 ].…”
Section: Discussionmentioning
confidence: 99%